Pengaruh Earning Per Share Dan Dividend Per Share Terhadap Harga Saham Perusahaan Subsektor Infrastruktur Yang Terdaftar Di BEI Tahun 2022-2024 - Muthia Azzalya; Eel Mutiaroh; Nadira Wulan Safitri; Syifa Rahma Maudy; Hana Nabila Rahmadani (Kampus Akademik Publiser, 2026)
This study aims to analyze the impact of Earnings Per Share (EPS) and Dividend Per Share (DPS) on the stock prices of infrastructure sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Employing a descriptive-quantitative method, the study selected a sample of 17 companies using purposive sampling. Secondary data were analyzed via multiple linear regression using IBM SPSS 27. Partial analysis revealed that EPS has a significant positive effect on stock prices; similarly, DPS exerts a significant positive influence, playing a more dominant role in driving stock prices. Simultaneously, both variables had a significant impact, with a coefficient of determination of 71.3%, while the remaining variance was attributed to other factors. In conclusion, operational profitability and dividend distribution policies are key drivers of equity market value fluctuations. Practically, the study suggests that investors should closely monitor cash dividend consistency to safeguard investments in the infrastructure sector, which is known for high volatility. For management, maintaining operational efficiency is crucial to ensuring net profit stability and upholding market confidence.